(untitled) (Comprehensive Journal of Science, 2026)
Terrorism is a renewed and changing phenomenon, its patterns change in different security and ages, which has imposed on contemporary criminal policy to go beyond traditional frameworks based on punishment alone, towards opening up to more flexible and effective preventive legislative mechanisms, but the real challenge remains in finding a balance between protecting national security and guaranteeing the fundamental rights and freedoms of individuals. The development of criminal policy in the face of terrorism requires a distance from traditional treatments and the adoption of a comprehensive approach based on the integration of legislation, prevention and international cooperation, to ensure greater effectiveness in the face of this diverse and renewed phenomeno